First Reported Case of a Well-Differentiated Neuroendocrine Tumor (WDNET) Arising Within Diffuse Ganglioneuromatosis (DGN) in a Patient With Neurofibromatosis Type 1 (NF-1). (11th September 2019) - Cox, Brian; Balzer, Bonnie; Dhall, Deepti; Guindi, Maha; Gangi, Alexandra; Larson, Brent
Abstract: Case Report: A 51-year-old female with NF-1 underwent flexible sigmoidoscopy, which revealed a 1.8-cm mass in the upper rectum. The noncircumferential mass was located predominantly at the posterior rectal wall and was suspicious for a neurofibroma. The biopsy revealed a WDNET arising in a ganglioneuroma that extended to the edges of the biopsy tissue. The patient underwent a segmental resection, and sections revealed residual grade 1 WDNET intimately admixed with DGN. The area of DGN also showed multifocal microscopic clusters of neuroendocrine cells limited to the lamina propria. Discussion: NF-1 involves the gastrointestinal tract in 10% to 25% of affected individuals. DGN is a poorly circumscribed, frequently transmural gastrointestinal lesion composed of spindled and ganglion cells that may be seen in PTEN hamartomatous tumor syndrome, multiple endocrine neoplasia syndrome type 2B, and (less commonly) NF-1. Though malignant transformation of neurofibromas to malignant peripheral nerve sheath tumors is well documented in NF-1, malignant transformation of DGN is extremely rare. To our knowledge, this is the first reported case of a WDNET arising in DGN. In addition to being the first reported case of WDNET in this setting, this is the first case to describe microscopic neuroendocrine cell nests in DGN. Similar proliferations have been described in the setting of inflammatory bowel disease, termed microcarcinoid or neuroendocrine cell micronests, which are not thought to have malignant potential. However, given the presence of these microscopic neuroendocrine cell nests within the larger DGN lesions and adjacent to the WDNET, we hypothesize that in the setting of NF-1, microscopic neuroendocrine cell clusters may serve as a precursor of WDNET. While this is a rare situation, these novel findings should prompt careful examination for WDNET and microscopic neuroendocrine cell nests in future cases of DGN.